The Cost of Forecast Errors in Company Sales Forecast - Dittmann, Paweł (Koszty błędów prognoz w prognozowaniu sprzedaży w przedsiębiorstwie, 2010)
To ensure company success on the market, managers need to design and employ a variety of forecasts. One of the most important forecasts for any company is the sales forecast. Similarly to other types of prognostic tools, sales forecast may be burdened with errors. Any such error will bear cost, resulting from the difference between demand for company products and their supply. Sum of such costs will influence company financial standing. This paper addresses the need to consider potential errors in the process of company sales forecasting and postulates a method for error evaluation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 35-42
Keywords: forecasting; forecast error; cost of forecast error